Laminate composite-based highly durable and flexible supercapacitors for wearable energy storage. (June 2020) - Anjum, Nasim; Grota, Matthew; Li, Dapeng; Shen, Caiwei
Highlights: Flexible supercapacitor is designed as a composite of electrolyte matrix and electrode filler. Mechanical and electrochemical performance can be optimized simultaneously. The prototype shows high capacitance with practical durability and flexibility. Abstract: Flexible supercapacitors are promising power sources for next-generation flexible electronics because they are safe, mechanically stable and durable compared with current batteries. However, flexible supercapacitor devices reported so far have not demonstrated adequate mechanical properties to withstand critical deformations for real-world applications. Here we present our design and construction of flexible supercapacitors using laminate composites to achieve exceptional mechanical properties, including foldability, twistability, and machine washability. The electrode layer is made of a polymer electrolyte/carbon electrode (matrix/filler) composite, with mechanical and electrochemical performance optimized simultaneously in its making. Calculations and experimental results show that proper volume ratio of the electrolyte matrix and fiber-based electrode fillers leads to desired flexibility, strength, as well as high areal capacitance. The prototypes show adjustable areal capacitances of over 40 mF/cm 2 with comparable thickness and flexibility to wearable fabrics. The electrochemical performance has remained unchanged after repeated folding and twisting tests. Moreover, a prototype device sewed onto a wearable fabric show non-detectable mechanical damage or capacitance degradation after machine washing. Graphical abstract: Image, graphical abstract